FFR- and Angiography-Guided Provisional Side Branch Stenting Offer Similar Benefits - Vinall, Maria (MD Conference Express, 2014)
Results of the Comparison of FFR-guided and Angiography-guided Provisional Stenting for True Coronary Bifurcation Lesions: A Randomized, Multi-center Clinical Trial [DKCRUSH-VI] show that fractional flow reserve (FFR)-guided and angiography-guided provisional side branch stenting of true coronary bifurcation lesions are associated with similar rates of 1-year major adverse cardiac events.